Peran Fungsi dan Tugas Masyarakat dalam Pendidikan: Kajian QS. Al-Ma’un - Yulianti, Ayu; Rikaeni, Ike; Amrullah, Fikri; Djazimi, M.A; Hidayat, Wahyu (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The role, duties and functions of society in education are very important. There is still a lack of sensitivity in the roles, duties and functions of society in education. Not many local people in the research location have studied up to university. There is still a lack of religious values in the surrounding environment. In QS Al-Ma'un, it states the characteristics of people who deny religion. There are still people who don't care about each other. In QS Al-Ma'un, it is also stated "so woe to those who pray, namely those who are negligent in their prayers, those who do riya, and are reluctant to provide assistance." Many people also do not understand the role, duties and functions of society in education. Therefore, this research was carried out using qualitative research methods because of the interaction between researchers and the surrounding community which was the research location.